AKUNTABILITAS MASJID JAMI BAITUL MUSLIMIN - DEWI ASMASARI, WANITA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to determine the Accountability of the Masjid Jami Baitul Muslimin. The research method used is the pheno menological approach. This study intends to find out the transparency and financial accountability of mosques managed by mosque administrators. The data in this study were obtained through direct interviews with informants directly related to the object of research, the Masjid Jami Baitul Muslimin. The results of this study indicate that the financial statements of the Masjid Jami Baitul Muslimin are still relatively simple in the form of recording cash in and cash out. This is a form of accountability or accountability and transparency of mosque finances. Analysis of sharia enterprise theory on the accountability of the Masjid Jami Baitul Muslimin has an understanding that the aspects of Habbluminallah or vertical accountability can be seen from the value of sincerity. In the aspect of Habluminannas or horizontal accountability seen from the value of education, economics, and the value of mutual cooperation. In the aspect of Habluminalaq seen from the value of cleanliness. Keywords: Accountability; Mosque; Shariah Enterprise Theory